ANALYSIS OF PALLIATIVE NURSING CARE FOR POST-OP CRANIOTOMY A/I SPONTANEOUS INTRACEREBRAL HEMORRHAGE (ICH) PATIENTS WITH PAIN MANAGEMENT INTERVENTION IN THE ICU OF ROYAL PRIMA HOSPITAL MEDAN IN 2026 - Cut Lianda Faradila; Idaman Kristiani Waruwu; Noniatri Ziliwu; Putri Nurul Izzah Andini; Seni Rofil Sandyani Mendrofa; Basri (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Intracerebral Hemorrhage (ICH) is a critical neurological condition with a high mortality rate that often requires craniotomy and intensive care in the ICU. Post-craniotomy patients generally experience acute pain that can worsen neurological conditions if not optimally managed. This study aims to analyze palliative nursing care in post-op craniotomy patients due to spontaneous intracerebral hemorrhage with pain management interventions in the ICU of Royal Prima Medan Hospital in 2026. The study used a case study method with a nursing process approach. The study population was post-op craniotomy patients with ICH in the ICU, with a sample of one 56-year-old female patient. Data collection was carried out through observation, physical examination, family interviews, and medical record documentation. The pain assessment instrument used the Critical Care Pain Observation Tool (CPOT), while data analysis was conducted descriptively. The results showed a decrease in CPOT pain scores from 7 to 5 after the administration of pharmacological and non-pharmacological pain management interventions. Patients also showed more stable hemodynamic conditions and a reduced response to the ventilator. The conclusion of the study shows that palliative nursing care with a focus on pain management is effective in helping to increase comfort and support the stability of the condition of post-craniotomy patients with ICH in the ICU.